Efficacy of cinnamon supplementation on glycolipid metabolism in T2DM diabetes: A meta-analysis and systematic review - Zhou, Qian; Lei, Xingxing; Fu, Shunlian; Li, Zinan; Chen, Yiding; Long, Cong; Li, Suwen; Chen, Qiu (Frontiers in Physiology, 2022)
Background: Cinnamon is a spice used in cooking and in large quantities as a medical complement with hypoglycemic and lipid-lowering properties. The potential pharmacological mechanisms underlying cinnamon’s anti-diabetic properties and its active ingredients have not been adequately determined. The current meta-analysis aims to systematically review the potential pharmacological mechanisms underlying the hypoglycemic and hypolipidemic efficacy of cinnamon administration and summarize clinical recommendations of cinnamon and its active ingredients. Method: Relevant randomized clinical trials (RCTs) were identified through a literature search that spanned the years January 2005 to April 2022. Retrieve electronic databases including Web of Science, PubMed, Embase, Medline, and the Cochrane Library. To obtain standardized mean differences (SMDs), continuous outcomes were pooled and 95 percent confidence intervals (CIs) were provided. Categorical outcomes were aggregated to calculate relative risks (RRs) and were accompanied by 95% CIs. Heterogeneity was measured using the Cochrane Q-test and I2 statistics, with a p < 0.05 considered as substantial heterogeneity. If I2 was less than 50%, a fixed effect model was employed; otherwise, a random effect model was used. Subgroup analyses and sensitivity analyses were performed to identify the origins of heterogeneity. Publication bias was retrieved by means of a funnel-plot analysis and Egger’s test. The data were analyzed using revman (V.5.3) and stata (V.15) software packages. Results: These 16 RCTs included a total of 1,020 patients who were followed for a duration ranging from 40 days to 4 months. According to the current meta-analysis results, glycolipid levels in diabetic individuals who received cinnamon were significantly improved as compared to those who got placebo (All p < 0.05). An adverse effect was only detected in one patient. Conclusion: These findings imply that cinnamon has a significant influence on lipid and glucose metabolism regulation. An even more pronounced effect was observed in patients with HbA1c of 8%. The results of this study suggested that cinnamon may be utilized as hypoglycemic and lipid-lowering supplement in clinical settings with a guaranteed safety profile.Systematic Review Registration: [PROSPERO], identifier [CRD42022322735].